Staphylococcus aureus biofilm activates the nucleotide‐binding oligomerization domain containing 2 (Nod2) pathway and proinflammatory factors on a human sinonasal explant model. Issue 11 (26th August 2013) - Cantero, Daniel; Cooksley, Clare; Bassiouni, Ahmed; Wormald, Peter‐John; Vreugde, Sarah
<x xml:space="preserve">Abstract</x> Background The presence of Staphylococcus aureus biofilms on sinonasal mucosal surfaces is associated with recalcitrant chronic rhinosinusitis (CRS), but little is known about the innate immune response they trigger. We aimed to study the human pattern recognition receptor (PRR) nucleotide‐binding oligomerization domain containing 2 (Nod2) receptor and downstream pathway in response to initial S. aureus biofilm infection. Methods Using a validated protocol, sinonasal mucosae from 4 non‐CRS donors were cultured with and without S. aureus biofilms and planktonic cells. After 24 hours, RNA was extracted and gene expression was analyzed using a human antibacterial response polymerase chain reaction (PCR) array. Immunohistochemistry was performed to confirm the presence and determine the immunolocalization of selected proteins. Results C‐X‐C motif (CXC) chemokine ligands 1 and 2, interleukin‐6 (IL‐6), and genes related to the Nod2 pathway were significantly upregulated in biofilm‐treated tissues compared with control samples. Nod2 pathway–specific gene expression was increased in biofilm‐treated tissues compared with planktonic S. aureus–treated explants. Enhanced expression of Nod2 and nuclear factor kappa B1 (NF‐κB1) was also detected with immunohistochemistry in control and biofilm‐treated tissues. Conclusion S. aureus biofilms exerted a proinflammatory response in the mucosa and activation of the Nod2 pathway, indicating this receptor to be involved in the innate immune response to S. aureus biofilms. Further studies are required to elucidate the role of this pathway in CRS.